Review paperLow cholesterol diet - Kobus, Grażyna; Bachórzewska-Gajewska, Hanna; Kinalska, Ida (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2009)
Improper food model, characteristic of high consumption of highly processed foods, animal fats among others, low consumption of fruit and vegetables, excess sodium consumption, increases the risk of developing cardiovascular diseases. Bad eating habits often lead to lipid economy disorder which is one of the coronary artery disease risk factors. Among people with excess level of cholesterol in blood the crucial method of treatment is always diet with reduced consumption of saturated fatty acids. In this review we present the basics of low cholesterol diet which is associated with the same idea as rational eating. In patients with lipids metabolism disorder we should reduce carbohydrates consumption as well as saturated fatty acids (NKT) along with food cholesterol which are thought to raise the concentration of LDL cholesterol and at the same time we should also increase the supply of fibre as well as plant fitosterol. The aim of this paper is also to display the examples of menu for people with hypercholesterolemy.